SOCIAL MEDIA MARKETING IN THE PROMOTION OF INCUBATOR BUSINESS PROGRAMS - Herawati, Andi Febri; Yusuf, Muhammad; Cakranegara, Pandu Adi; Sampe, Ferdinandus; Haryono, Andri (JURNAL DARMA AGUNG, 2022)
One of the reasons the government will continue to implement public information disclosure is the public's lack of understanding and knowledge about government service programs. As one of the government agencies that provides public services, the Bandung Industrial Training Center uses social media platforms such as Instagram, Facebook, and WhatsApp as marketing media to provide information and market the Business Incubator program. According to Gunelius, the concept of implementing Social Media Marketing is used to analyze the implementation of Social Media Marketing, namely Content Creation, Content Sharing, Connecting, and Community Building. The goal of this study is to identify and analyze how the Bandung Industrial Training Center uses Social Media Marketing to promote the Business Incubator program. The descriptive qualitative research method was used, as well as the constructivism paradigm. The Bandung Industrial Training Center, according to the findings, implemented four critical elements that contributed to the success of Social Media Marketing: Content Creation, Content Sharing, Connecting, and Community Building. However, the application in the three social media platforms remains unbalanced, and the use of features in each social media platform is inefficient. This article uses terms such as business incubator, public service, and social media marketing.